Evaluation of FC1×FC2 Silkworm Hybrid Performance on Diverse Mulberry Varieties - Kumar, Nitish L. S.; Sugeetha, G.; Asha, N. N.; Kumar, L. Vijay; Sadafale, Gaurav Vinod Rao (International Journal of Economic Plants, 2026)
The experiment was conducted during rabi, October, 2024–January, 2025 at the College of Agriculture, V. C. Farm, Mandya, to assess the effect of different mulberry (Morus spp.) varieties on the biological and economic performance of the silkworm Bombyx mori (FC1×FC2 double hybrid). Sericulture productivity was strongly dependent on the nutritional composition and palatability of mulberry leaves; therefore, the identification of suitable mulberry cultivars was considered essential for enhancing cocoon yield and silk quality. A laboratory-based Completely Randomized Design consisting of eight treatments with three replications was followed, with each replication comprising 50 larvae. The mulberry varieties evaluated included Mysore Local, Sahana, S36, DD, AR12, V1, G2 and G4, all of which were cultivated under uniform agronomic and maintenance practices to ensure experimental consistency. Statistically significant differences were observed among the varieties for larval weight, cocoon weight, shell weight, shell ratio, and filament denier. Among the tested cultivars, V1, DD and G4 produced significantly heavier cocoons and higher effective rearing rates, whereas Mysore Local recorded the lowest values for most economic traits. Cocoon shell weight and shell ratio were highest in V1, G2 and DD, indicating superior silk deposition efficiency and better nutrient utilization. Filament denier also varied considerably, with V1 yielding relatively thicker and stronger filaments. Overall, the results revealed that high-yielding mulberry varieties such as V1, G2, DD, and G4 markedly improved cocoon productivity and filament quality, demonstrating their suitability for commercial rearing of the FC1×FC2 silkworm hybrid under controlled rearing conditions.